2007
DOI: 10.1530/eje.1.02346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GH on cognitive function in elderly patients with adult-onset GH deficiency: a placebo-controlled 12-month study

Abstract: Objective: Young adults with childhood-onset GH deficiency (GHD) have reduced memory and attention, which can be improved by treatment with GH. Little information is available on cognitive function in elderly GHD patients. Design: Single center, double-blind, randomized, placebo-controlled study of 52-week duration. Methods: Elderly GH therapy naïve GHD patients (nZ34; age range 60-77 years) were enrolled and randomized to receive placebo or GH therapy which was titrated to achieve a target IGF-I level of C1 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 49 publications
2
37
1
1
Order By: Relevance
“…This difference between the GH and the placebo group occurred because of both an increase in cognitive function in the GH-treated group and a decrease in the placebo group. After 52 weeks of treatment, however, there were no significant differences in psychological performance between the GH-treated group and the placebo group (31).…”
Section: Cognition In Adults With Ao-ghdmentioning
confidence: 75%
“…This difference between the GH and the placebo group occurred because of both an increase in cognitive function in the GH-treated group and a decrease in the placebo group. After 52 weeks of treatment, however, there were no significant differences in psychological performance between the GH-treated group and the placebo group (31).…”
Section: Cognition In Adults With Ao-ghdmentioning
confidence: 75%
“…In almost all of these studies, the benefits of GH were revealed by some, but not all instruments employed and/or were attributed to certain, but not all, dimensions measured; finally, they seemed to be heavily dependent on the degree of the initial impairment and were partly related to placebo effect. On the other hand, in the studies by Cuneo et (26) no change in QoL in the treated patients was found.…”
Section: Introductionmentioning
confidence: 79%
“…In addition, the higher tendency of IGF1/GH ratios in the elderly group than others was found in female but not male patients. In patients with GH deficiency, it has been reported that the gender difference remains in elderly patients, i.e., women above 60 years have lower IGF1 than men, in spite of similar GH secretion (12). Therefore, it is interesting to note the relatively higher IGF1 levels in elderly female patients with acromegaly.…”
Section: Young (%30 Years)mentioning
confidence: 94%